OCCUPATIONAL SAFETY RISK MANAGEMENT OF RAGUNAN ZOO STAFF BASED ON ISO 31000 - Gea Alzera Kosanda; Dominicus Savio Priyarsono; Tanti Novianti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Ragunan Wildlife Park (TMR) is one of the largest zoos in Indonesia which is a public body managed by the DKI Jakarta local government facing challenges in managing staff occupational safety risks, especially those who interact directly with dangerous animals. Some of the accidents that occurred showed that the existing safety procedures were not fully effective. This study aims to evaluate the implementation of ISO 31000-based occupational safety risk management in TMR and provide recommendations for improvement of existing systems. This study uses a qualitative approach with a case study design, involving interviews with staff, direct observation, and document analysis related to risk management implemented in TMR. The data obtained were analyzed using the ISO 31000 framework to assess the effectiveness of risk management and identify areas that need to be improved in occupational safety procedures. The results show that TMR has identified a wide range of safety risks, such as wild animal attacks, work equipment accidents, and fire risks. The implementation of ISO 31000 in risk management helps improve safety procedures by improving staff training, the use of appropriate personal protective equipment (PPE), and regular risk evaluation. However, there are still challenges in terms of communication between staff, supervision, and readiness to face emergency situations. The implications of this study show that the application of ISO 31000 can be a more systematic basis in managing safety risks in TMR. This research makes an important contribution to improving staff occupational safety and provides recommendations for more effective risk management, which in turn supports the smooth operation and sustainability of conservation programs at TMR.